Analisis Pengaruh Pendapatan Ijaroh Muntahiyyah Bit Tamlik dan Murabahah Terhadap Tingkat Profitabilitas Pada PT Bank Syariah Indonesia Periode 2021-2023 - Efendi, Agus; Ahoen, Bahori; Handayani, Agustia (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2024)
This research aims to determine the effect of IMBT and Murabahah on the level of profitability of Islamic banks. Sharia Commercial Bank is a sharia bank which in its activities provides services in payment traffic. In Islamic banks there are several contracts used in transactions, namely: Mudharabah, Murabahah, Salam, Istisna, Ijaroh, Wadiah and so on. One of the things done in the banking business is to gain profit/profitability. Profitability is the bank's ability to obtain profits, one of the basic tools is using ROA (Return On Assets). This research is quantitative descriptive research, based on secondary data taken from PT Bank Syariah Indonesia publication reports for 2021-2023, then data analysis techniques were processed using the SPSS application by carrying out classic assumption tests and multiple regression tests. The research results show that IMBT does not have a significant influence on profitability, whereas on the other hand, murabahah has a significant influence on the level of profitability of Bank Syariah Indonesia in 2021-2023.